Impact of High-risk Features and Effect of Neoadjuvant Chemotherapy in Urothelial Cancer Patients with Invasion into the Lamina Propria on Transurethral Resection in the Absence of Deep Muscle Invasion - Metcalfe, Michael J. (Eur Urol Focus, 2017)
BACKGROUND: High-risk non–muscle-invasive bladder cancer (NMIBC) that invades into the lamina propria is frequently understaged and is associated with a risk of lymph node metastasis and death. OBJECTIVE: To identify high-risk features (HRFs) for NMIBC that may identify patients with poorer prognosis who may benefit from neoadjuvant chemotherapy (NAC) prior to radical cystectomy (RC). DESIGN, SETTING, AND PARTICIPANTS: We performed a single-center retrospective review of patients who underwent RC for NMIBC with invasion into the lamina propria between 1995 and 2013. HRFs included hydronephrosis, abnormal examination under anesthesia, lymphovascular invasion, or variant histology. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: Pathology at RC, and overall (OS) and disease-specific (DSS) survival were evaluated and analyzed by Fisher’s exact test, Student t test, Cox proportional hazards regression analysis, and the Kaplan–Meier method. RESULTS AND LIMITATIONS: We identified 336 patients with a median follow-up of 130 mo. Of these, 159 (47%) had no HRF, 140 (41.5%) had one HRF, and 37 (11%) had ≥2 HRFs. At RC, patients with ≥2 HRFs had a significantly higher rate of pathologic T stage upstaging and lymph node metastasis (p < 0.05). Median OS was 139 mo for those with no HRF, 127 mo for those with one HRF, and 56 mo for those with ≥2 HRF (p = 0.0057). HRFs are also associated with a decreased DSS (p = 0.0009). Patients with ≥2 HRFs (11/37) who received NAC showed improved OS (21% vs 55% 5-yr OS, p = 0.0353) and trended toward an improvement in DSS (25% vs 56% 5-yr OS, p = 0.0716) compared with RC alone. CONCLUSIONS: The presence of ≥2 HRFs in NMIBC invading the lamina propria is associated with worse pathology at RC and a significant decrease in OS and DSS. NAC appears to provide benefit for these patients. Limitations include retrospective design and limited sample size. PATIENT SUMMARY: The presence of high-risk features in urothelial cancer with invasion into the lamina propria has a worse prognosis that may be mitigated by neoadjuvant chemotherapy.